Formación del Profesorado y Justicia Social en el Siglo XXI: Dos Conceptos Controvertidos - David Lee Keiser (Universidad Autónoma de Madrid, 2016)
In 2016, it seems impossible to stipulate that the basic aim of a thoughtful and engaged citizenry for the United States is shared by all. But irrespective of political spectacle, forces of social and cultural reproduction play out in public schools and universities, and often experiences and realities are located and interpreted to privilege an instrumental, quantitative, and some would say narrow construction of the purpose of schooling. This short essay addresses two tropes within education: teacher education (i.e. the ways in which teachers are prepared) and social justice (i.e. one means to an end for such preparation). The current social and political climate in the United States demands that these respective terms stay salient with regard to the needs of children in public schools. Said another way, both social justice and teacher education have become contested concepts. Are they compatible, or is their consonance an educational chimera?